Analisis Strategi Pemasaran Digital dalam Meningkatkan Brand Awareness Amanda Brownies Kota Samarinda - Meinaya Putri Syahvina; Kadori Haidar; Noor Ellyawati; Indah Permatasari (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The rapid advancement of information technology has encouraged companies to adopt digital marketing as a strategic approach to enhancing consumer brand awareness. Amanda Brownies Samarinda has utilized various digital platforms; however, the effectiveness of the implemented strategies requires further examination. This study aims to analyze the digital marketing strategies employed by Amanda Brownies Samarinda, their role in enhancing brand awareness, and the factors that support and hinder their effectiveness. A qualitative descriptive approach was employed in this research. Data were collected through observation, structured interviews, and documentation, and subsequently analyzed using the Miles, Huberman, and Saldaña model. The findings reveal that Amanda Brownies Samarinda implements an integrated digital marketing strategy through seven platforms, namely Instagram, Facebook, TikTok, WhatsApp Business, GoFood, GrabFood, and ShopeeFood. These strategies contribute to enhancing brand awareness through four dimensions: recognition, recall, purchase, and consumption. Consistency in visual identity, promotional intensity, ease of access to information, transaction convenience, product quality, and consumer engagement were identified as the primary factors supporting the success of digital marketing implementation. Nevertheless, the utilization of TikTok has not yet been optimized compared to the other platforms. The novelty of this study lies in its comprehensive analysis of the role of integrating seven digital platforms in enhancing brand awareness through the dimensions of recognition, recall, purchase, and consumption, thereby providing a more holistic understanding of digital marketing effectiveness within the culinary industry, particularly at Amanda Brownies Samarinda.